A Study on the Usability of Moodle and Blackboard – Saudi Students Perspectives - Alghafis, Aseel; Alrasheed, Atheer; Abdulghany, Amal (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Nowadays, e-learning management systems are used in many universities around the world. In Saudi Arabia, universities use several systems such as Moodle and Blackboard. However, only little empirical research has been conducted on Saudi students’ preference for such systems. This study compared the usability of Moodle and Blackboard systems among Saudi university students. Specifically, three comparison metrics have been considered: user interface, download and upload service and materials organization. The results showed that the students preferred Moodle and believed that it is more usable than Blackboard in all studied metrics.